Factors of dynamics of social institutions - Savka, Viktor (Ukrainian Sociological Journal, 2015)
In the article, based on the analysis of foreign and local authors’ publications, including representatives of neo-institutional direction was made an attempt to identify the main factors of transformations of social institutions and institutional system in the context of modernization processes that take place in the Ukrainian society. Transformation of values accepted by the society is considered as a major factor in the system of these factors. Except for this, such factors as conflict between the essential content and institutionalization of social institutions, the effect of social institutions agents (individual and group) are analyzed in the article. Also the problem of different levels of rationality as a factor of modernization of today’s society, which attributive features are uncertainty and progressive individualization of social life.